Current concepts regarding Graves' orbitopathy. (1st June 2022) - Bartalena, Luigi; Tanda, Maria Laura
Abstract: Graves' orbitopathy (GO) is an orbital autoimmune disorder and the main extrathyroidal manifestation of Graves' disease, the most common cause of hyperthyroidism. GO affects about 30% of Graves' patients, although fewer than 10% have severe forms requiring immunosuppressive treatments. Management of GO requires a multidisciplinary approach. Medical therapies for active moderate‐to‐severe forms of GO (traditionally, high‐dose glucocorticoids) often provide unsatisfactory results, and subsequently surgeries are often needed to cure residual manifestations. The aim of this review is to provide an updated overview of current concepts regarding the epidemiology, pathogenesis, assessment, and treatment of GO, and to present emerging targeted therapies and therapeutic perspectives. Original articles, clinical trials, systematic reviews, and meta‐analyses from 1980 to 2021 were searched using the following terms: Graves' disease, Graves' orbitopathy, thyroid eye disease, glucocorticoids, orbital radiotherapy, rituximab, cyclosporine, azathioprine, teprotumumab, TSH‐receptor antibody, smoking, hyperthyroidism, hypothyroidism, thyroidectomy, radioactive iodine, and antithyroid drugs. Recent studies suggest a secular trend toward a milder phenotype of GO. Standardized assessment at a thyroid eye clinic allows for a better general management plan. Treatment of active moderate‐to‐severe forms of GO still relies in most cases on high‐dose systemic—mainly intravenous—glucocorticoids as monotherapy or in combination with other therapies—such as mycophenolate, cyclosporine, azathioprine, or orbital radiotherapy—but novel biological agents—including teprotumumab, rituximab, and tocilizumab—have achieved encouraging results. Abstract :